Cutaneous Manifestations in Pancreatic Diseases—A Review - Miulescu, Raluca (J Clin Med, 2020)
Pancreatic pathology, comprising acute and chronic pancreatitis, autoimmune pancreatitis and pancreatic neoplasms, primarily presents with gastrointestinal symptoms and signs; however, it is well recognized that it can also associate a wide range of extra-digestive features. Among these systemic manifestations, cutaneous involvement plays an important role both as a diagnostic clue for the pancreatic disease itself and serving as a prognostic factor for the severity of the condition. Recognition of these cutaneous signs is, however, far from being satisfactory, all the more as some of them are relatively rare. In the current review, we discuss skin involvement in pancreatic diseases, referring to pancreatic panniculitis, cutaneous hemorrhagic manifestations, skin metastasis, acanthosis nigricans, livedo reticularis, necrolytic migratory erythema and cutaneous fistula. We highlight the clinical characteristics, treatment and prognostic value of these lesions. Better awareness among medical specialties other than dermatology is needed for detection of the skin clues associated with pancreatic pathology.